Verdis Opern und der Risorgimento - Walter, Michael (Muzikološki zbornik, 2014)
The thourough analysis of historical sources from the beginning of the year 1859 shows that the famous acrostic VIVA VERDI was not only widely known in Italy but also throughout Europe. However, it was not associated with any political activities of the composer Giuseppe Verdi. The reason is that Verdi's operas already during the revolutionary months of 1848 were not understood as political "Risorgimento" operas. The causes for political demonstrations during performances of Verdi's operas were either coincidentally or provoked by political circumstances which were independent of the operas. Verdi's operas were, in any case, not the causes of spontaneous patriotic emotions.
Keywords: 1848; Attila; Ghislanzoni, Antonio, 1824-1893; Italija; Italy; Nabucco; opera in politika; revolucija; risorgimento; Verdi, Giuseppe, 1819-1901; zedinjenje Italije